The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11605-008-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

Total Gastrointestinal Tract Necrosis After Ingesting a Considerable Amount of Hydrochloric Acid

Abstract: Computed tomography (CT) scan showed significant free air in the neck, lateral esophagus, and abdominal cavity, which indicated perforation of the esophagus and gastrointestinal tract. In addition, the abdominal CT image showed splenic subcapsular hematorna and swollen pancreatic head caused by strong acid causis. We found the entire gastrointestinal tract from stomach to rectum necrosis in the emergency exploratory laparotomy. Our case suggests that ingestion of a considerable amount (e.g., 500 mL) and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the present case dilution of acid with alcohol has lead to a significant corrosive injury to the proximal jejunum rather when compared to the oesophagus or the stomach. However it has been reported that strong acids when taken in considerable amount can lead to injury beyond the stomach causing extensive necrosis of the small intestine and colon [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case dilution of acid with alcohol has lead to a significant corrosive injury to the proximal jejunum rather when compared to the oesophagus or the stomach. However it has been reported that strong acids when taken in considerable amount can lead to injury beyond the stomach causing extensive necrosis of the small intestine and colon [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The site, extent and intensity of damage depend on the multiple factors related to the caustic agent, duration of contact and the victim [4]. Concomitant acid injury of the lower gastrointestinal tract is a rare occurrence due to acid induced pylorospasm with consequent gastric pooling, and neutralizing effect of the bile [1,[5][6][7]. However, isolated necrosis of the lower gastrointestinal tract with relative sparing of the proximal gastrointestinal tract is extremely rare with limited reports [2,4,5].…”
Section: Introductionmentioning
confidence: 99%